2020
DOI: 10.5798/dicletip.706022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of 8-Hydroxy-2-Deoxyguanosine And Malondialdehyde Levels In First-Trimester Miscarriage: A Prospective Cohort Study

Abstract: Objective: This study was aimed to evaluate 8-hydroxy-2-deoxyguanosine (8-OHdG) and malondialdehyde (MDA) levels in patients with first trimester miscarriage. Methods: This prospective cohort study included 35 women, who were diagnosed with miscarriage (patient group) and 35 healthy pregnant women below 14 weeks of gestation (control group), who did not report any complaints. 8-OHdG levels were measured with a competitive ELISA (Enzyme-Linked ImmunoSorbent Assay) high sensitivity kit and MDA levels were also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Enhanced production of 8-OHdG in RPL group is reflective of the DNA damage accountable for pregnancy termination in these patients. The data obtained here, is in accordance with previous finding ( Gunduz et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…Enhanced production of 8-OHdG in RPL group is reflective of the DNA damage accountable for pregnancy termination in these patients. The data obtained here, is in accordance with previous finding ( Gunduz et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress (OS) occurs due to an elevation in the levels of free radicals, production, and/or reactive oxygen species (ROSs), coupled with a decline in the biological system's ability to efficiently e liminate the reactive intermediates or repair the resulting damage. Because OS plays a pathophysiologic role in the placental enzymes and fetus, increased free radical activity is seen in pregnant women with conditions like preeclampsia, spontaneous abortion, and intrauterine growth restriction [27].…”
Section: Malondialdehyde (Mda) and Miscarriagesmentioning
confidence: 99%
“…Most studies point out that 8-OHdG is an oxidative base adduct and a predictive biomarker for oxidative induce DNA damage in the sperm [ [25] , [26] , [27] , [28] ]. A prospective cohort study suggested that 8-OHdG and MDA influence the etiopathogenesis of first-trimester miscarriage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%